التطورات السياسية الداخلية في سنغافورة 1945 – 1959 والموقف البريطاني منها - حاتم الفهد, ماهر جاسب (Journal of College of Education, 2018)
This Research deals with the Internal Political Developments in Singapore from 1945 to 1959. During this period, Singapore witnessed significant Political Transformations, which had a profound impact on the achievement of its self-rule in 1959 and Partly eliminated it from the domination of British Colonialism . This stage witnessed clear Cooperation between most of the Singaporean figures and elites on the one hand and the British authorities on the other, with regard to most of the projects and political steps in Singapore. Only some leftist elements (especially communism ) stood against them .This cooperation resulted in Gradual progress in the political and constitutional status of Singapore. It was transformed from a colony directly administered by the British General Governor to a self-governing state governed by a Singaporean prime minister and supported by an elected Legislative Assembly of the Singaporean People .The cooperation between the two sides also had a clear impact on the Political Situation in Singapore . For the first time in the history of Singapore, Political Parties emerged to Contain and Organize the masses . The most important of these parties were the Malian Democratic Union, the Progressive Party, the Labor Front and the People's Action Party . The number of its members in the 1959 elections reached 13, and this cooperation also resulted in the writing of the First Constitution in The country. The process was formulated in a number of stages and then finalized in 1958 . Elected National Legislatures in the country; In which the political parties competed and their men competed to receive positions . On the other hand, this political stage was a reflection of the nature of the British deal with them . The political parties, especially the president ( the Action Front and the People's Action Party ), forced the British to respond to the most important demands of the people of Singapore, The period ( 1945-1959 ) dominated the Progressive Party in the 1948 and 1951 elections, then the Labor Front won the 1955 elections, and the People's Action Party swept everyone in the 1959 Elections